Ultrahigh-strength aluminum alloy powder material and preparation method and application thereof

By optimizing the composition of aluminum alloy powder materials and additive manufacturing process parameters, and combining laser powder bed melting method to prepare aluminum alloy workpieces, the problems of insufficient strength and cracking of additive high-strength aluminum alloys in the prior art are solved, and ultra-high strength and excellent mechanical properties are achieved.

CN119876707APending Publication Date: 2025-04-25CRRC IND INST CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411912879.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the strength of additively manufactured high-strength aluminum alloys is insufficient, and there are insufficient mechanical properties and cracking problems, making it difficult to meet high-performance needs in the fields of aviation, aerospace, etc.

Method used

By optimizing the composition and additive manufacturing process parameters of aluminum alloy powder materials, aluminum alloy powder materials of Mg6.5%~10.0%, Sc 0.7%~1.0%, Zr 0.4%~0.7%, Mn 0.40%~1.0%, Si 0.3%~0.7% were designed, and the vacuum induction smelting and high-flow atomization process were prepared, and the deposited aluminum alloy workpieces were prepared in combination with laser powder bed melting.

Benefits of technology

The tensile strength of aluminum alloy workpieces has exceeded the ultra-high strength level of 600MPa grade, and has higher density, strength, plasticity and fatigue resistance. It has no pores, cracks and microcracks. It has small grains and excellent formability and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876707A_ABST
    Figure CN119876707A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum alloys, and relates to an ultrahigh-strength aluminum alloy powder material and a preparation method and application thereof, in particular to an aluminum alloy powder material which comprises the following alloy elements in percentage by mass: 6.5%-10.0% of Mg, 0.7%-1.0% of Sc, 0.4%-0.7% of Zr, 0.40%-1.0% of Mn, 0.3%-0.7% of Si, less than or equal to 0.2% of trace elements and the balance of Al. The prepared aluminum alloy workpiece has high density, higher strength, plasticity and fatigue resistance and good yield ratio, and the aluminum alloy workpiece is free of air holes, cracks and microcracks, fine in grain and excellent in formability and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and particularly to an ultra-high-strength aluminum alloy powder material and a preparation method and application thereof, and in particular to an ultra-high-strength aluminum alloy and a laser additive manufacturing method thereof, which are suitable for ultra-high-strength aluminum alloy parts in military / civilian aerospace, aviation, rail transportation and other fields. Background Art

[0002] With each generation of materials, there is a generation of equipment. As the product structure design and manufacturing in the fields of aviation, aerospace, rail transit, wind power, weapons industry, automobile manufacturing, etc. gradually develop towards lightweight, high performance and integration, various special-shaped curved surface structures, thin-walled components and complex structures such as variable cross-section internal flow channels are increasingly widely used. The development trend of the integration, complexity and structural function integration of parts and components has put forward higher requirements on material performance and manufacturing processes. As an advanced manufacturing technology, metal additive manufacturing technology can realize the integrated rapid prototyping of micron-level fine structures, especially in the manufacturing of lightweight complex topological structures and multifunctional integrated structures, showing advantages that traditional manufacturing methods such as casting, forging and welding cannot achieve, and has become a key technology that countries around the world are competing to develop and apply. This technology has shown broad application prospects in the fields of cutting-edge equipment such as rail transit, aerospace, weapons and equipment, and has huge market potential. More and more high-end equipment designers are willing to adopt the concept of additive manufacturing, starting from the source of design and guided by functional requirements to drive the innovative design of parts and components. In particular, advanced manufacturing technologies with the theme of "lightweight high-performance materials + structural optimization design + additive manufacturing" have shown great development space in equipment manufacturing. Aluminum alloy additive manufacturing technology can well meet the urgent needs for lightweight, integrated and high-performance parts in the fields of aviation, aerospace, rail transportation, wind power, weapons, etc.

[0003] However, the existing commercially available 3D printing aluminum alloy powders are mainly AlSi7Mg and AlSi10Mg alloys, but the strength of these two types of alloys after printing is low, not exceeding 300MPa, and the elongation is not more than 10%, with problems of insufficient mechanical properties and limited alloy material types. Traditional high-strength forging alloys such as 2xxx and 7xxx series alloys are highly sensitive to hot cracks and show poor additive manufacturing mechanical properties, which is mainly attributed to the long solidification temperature range and high level of residual stress caused by the complex thermal history during the laser powder bed melting process. At present, the most effective strategy to solve the cracking problem is to develop a fine grain structure, a large number of grain boundaries (GB) destroy the stress generated during solidification, improve the resistance to hot cracking, and effectively inhibit cracks. At the same time, a large number of GBs will hinder dislocation movement and effectively improve mechanical strength. The main means at present are to introduce lattice-matched nucleating agent particles and / or contain effective solutes characterized by high growth restriction factors to trigger significant grain refinement. Combined with the non-equilibrium solidification characteristics during laser powder bed melting, cracks and grain refinement can be effectively suppressed, and crack-free, high-performance components are expected to be obtained.

[0004] In recent years, additively manufactured high-strength aluminum alloys represented by the addition of Sc / Zr have also received widespread attention and achieved some commercial success. These alloys, represented by Al-Mg-Sc-Zr alloys, have significantly refined microstructures and enhanced mechanical properties. Although grain refinement effectively strengthens the alloys in these alloys, for newly developed aluminum alloys, the strength is basically around 500MPa. At the same time, it is still a major challenge to obtain a satisfactory balance between strength and ductility. This challenge has hindered the wider commercial application of laser powder bed melting aluminum alloys. Summary of the invention

[0005] The present invention provides an ultra-high-strength aluminum alloy powder material and a preparation method and application thereof, so as to solve the defect of insufficient strength of high-strength aluminum alloy manufactured by additive manufacturing in the prior art. By optimizing the composition of the aluminum alloy powder material and the process parameters of additive manufacturing, the preparation of ultra-high-strength aluminum alloy workpieces is achieved, and the strength of the aluminum alloy workpiece can even exceed the ultra-high-strength level of 600MPa.

[0006] Specifically, the present invention provides an aluminum alloy powder material, wherein the alloy elements thereof include, by mass fraction, Mg 6.5%-10.0%, Sc 0.7%-1.0%, Zr 0.4%-0.7%, Mn 0.40%-1.0%, Si 0.3%-0.7%, trace elements less than or equal to 0.2% and Al balance.

[0007] The trace elements are selected from one or a combination of two or more of Ti, Fe, Ni, Cu, Cr, Zn and V.

[0008] Preferably, the content of each trace element is less than or equal to 0.03%.

[0009] According to the aluminum alloy powder material provided by the present invention, the particle size of the aluminum alloy powder material ranges from 15 μm to 60 μm; And / or, the average sphericity of the aluminum alloy powder material is greater than 0.85; And / or, the hollow powder rate of the aluminum alloy powder material is not more than 5%.

[0010] In the present invention, the mass percentage of oxygen element in the aluminum alloy powder material is lower than 0.1%, the hydrogen content is lower than 0.003%, the carbon content is lower than 0.009%, and the nitrogen content is lower than 0.03%.

[0011] In a second aspect, the present invention also provides a method for preparing the aluminum alloy powder material as described above, comprising: melting and atomizing aluminum raw materials, magnesium raw materials, Al-Si master alloys, Al-Sc master alloys, Al-Zr master alloys and Al-Mn master alloys according to the alloy element quality design of the aluminum alloy powder material.

[0012] According to the method for preparing the aluminum alloy powder material provided by the present invention, the smelting comprises: vacuum induction melting; Preferably, the vacuum degree of the vacuum induction melting is ≤0.5×10 -2 Pa; Preferably, the melting temperature of the vacuum induction melting is 850°C to 950°C; Preferably, the heating rate of the vacuum induction melting is 8°C / min to 20°C / min.

[0013] In a third aspect, the present invention further provides a deposited aluminum alloy workpiece, which is prepared by an additive manufacturing method, and the raw materials thereof include: the aluminum alloy powder material as described above, or the aluminum alloy powder material prepared by the preparation method as described above; the additive manufacturing method includes a laser powder bed melting method; Preferably, the deposited aluminum alloy workpiece has a tensile strength of 475 MPa to 515 MPa, a yield strength of 440 MPa to 490 MPa, and an elongation of 14% to 30%.

[0014] In a fourth aspect, the present invention further provides a method for preparing a deposited aluminum alloy workpiece, comprising: the raw materials thereof include: the aluminum alloy powder material as described above, or the aluminum alloy powder material prepared by the preparation method as described above; The raw material is deposited on an aluminum alloy substrate by a laser powder bed melting method to obtain the deposited aluminum alloy workpiece; Preferably, in the laser powder bed fusion method, the laser spot diameter is 100 μm, the laser power is 180 W to 380 W, the laser beam scanning speed is 800 mm / s to 1400 mm / s, the scanning interval is 0.10 mm to 0.15 mm, and the layer thickness is 25 to 40 μm; Preferably, the preheating temperature of the aluminum alloy substrate is 80°C to 160°C.

[0015] The present invention realizes powder making through vacuum induction melting gas atomization (VIGA). The obtained ultra-high strength aluminum alloy powder has less element burn-out, low hollow powder rate, low oxygen content, high sphericity, good fluidity, and uniform and controllable composition. The obtained ultra-high strength aluminum alloy powder meets the technical requirements of laser powder bed melting process and batch stability requirements, and is suitable for industrial manufacturing.

[0016] In a fifth aspect, the present invention also provides an aluminum alloy workpiece, which is obtained by preparing a deposited aluminum alloy workpiece by laser powder bed melting method and then performing aging treatment, and comprises: its raw materials include: the aluminum alloy powder material as described above, or the aluminum alloy powder material prepared by the preparation method as described above.

[0017] According to the aluminum alloy workpiece provided by the present invention, the microstructure of the aluminum alloy workpiece includes a bimodal grain structure of equiaxed crystals and columnar crystals, and discontinuous micron-sized Mg 2 Si、Al 6 Mn particles and nano-scale Al 3 (Sc, Zr) particles; Preferably, nanoscale Al 3 The average width of the (Sc, Zr) particles is 1.1nm~1.3nm.

[0018] According to the aluminum alloy workpiece provided by the present invention, the tensile strength of the aluminum alloy workpiece is greater than 600 MPa, the yield strength is greater than 560 MPa, and the elongation is greater than 8%; Preferably, the tensile strength is 600MPa~650MPa, the yield strength is 560MPa~630MPa, and the elongation is 8%~13%.

[0019] In a sixth aspect, the present invention further provides a method for preparing an aluminum alloy workpiece, wherein the aluminum alloy workpiece is prepared by a laser powder bed fusion method and then subjected to an aging treatment, wherein the raw materials include: the aluminum alloy powder material as described above, or the aluminum alloy powder material prepared by the preparation method as described above; Preferably, the deposited aluminum alloy workpiece is the deposited aluminum alloy workpiece as described above or a deposited aluminum alloy workpiece prepared by the preparation method as described above; Further preferably, the aging treatment includes: an aging temperature of 275°C to 375°C, a holding time of 1h to 8h, and air cooling; more preferably, the aging temperature is 275°C to 325°C, a holding time of 2h to 8h, and air cooling.

[0020] Further preferably, the aging treatment includes: aging temperature of 300° C., holding time of 4 hours, and air cooling.

[0021] The present invention provides an ultra-high strength aluminum alloy powder material and a preparation method and application thereof, by designing the alloy element composition, specifically: by mass fraction, the alloy elements include: Mg 6.5%~10.0%, Sc 0.7%~1.0%, Zr0.4%~0.7%, Mn 0.40%~1.0%, Si 0.3%~0.7%, trace elements less than or equal to 0.2% and Al balance. Based on the composition design, combined with the process optimization of additive manufacturing of the present invention, the obtained aluminum alloy workpiece has higher density, higher strength, plasticity and fatigue resistance, good yield strength ratio, no pores, cracks and microcracks, fine grains, excellent formability and mechanical properties.

[0022] More specifically, the present invention designs the composition of aluminum alloy materials based on crack resistance and synergistic strengthening of strength and plasticity. Among them, by increasing the Mg content, the formation of Al-Mg intermetallic compounds is promoted, and the nucleation and growth of the primary phase during solidification are promoted. The primary phase, as a heterogeneous nucleation particle, can achieve the effect of grain refinement. 3 The precipitation of (Sc, Zr) obtains a fine-grained structure and promotes the formation of a bimodal grain structure of equiaxed crystals and columnar crystals. By adding Mn elements to narrow the solidification range, promote the formation of eutectic phases, reduce the value of the crack sensitivity factor, and thus reduce the possibility of crack formation. By adding Si elements to accelerate the diffusion of Sc and Zr elements in the α(Al) (FCC) matrix, more low-melting-point eutectics are formed in the later stage of solidification to fill cracks. In addition, the addition of Si elements can also promote heterogeneous nucleation, increase the molar fraction of precipitated phases, refine grains, and hinder crack formation. The addition of Mg, Mn, and Si can also form discontinuous micron-sized Mg at the grain boundaries. 2 Si、Al 6 Mn particles, thereby providing dispersion strengthening contribution. The present invention also utilizes the characteristics of non-equilibrium rapid cooling of additive manufacturing to make Sc and Zr supersaturated solid solution in the matrix, thereby limiting the mechanical properties of the deposited state, so that the mechanical properties can be improved by further heat treatment process regulation. Furthermore, the aging treatment of the present invention makes the supersaturated solid solution Sc and Zr in the matrix in the form of nano-scale Al 3 The Zr(Sc, Zr) precipitates in the form of (Sc, Zr) particles, thus providing precipitation strengthening contribution.

[0023] The aluminum alloy workpiece produced by the present invention has broad application prospects in the fields of military / civilian aerospace, aviation, rail transportation, etc. The ultra-high strength aluminum alloy workpiece solves the key technical problems of low strength and cracking of aluminum alloy materials in additive manufacturing, expands the applicable scenarios of aluminum alloy additive manufacturing technology, and can meet service requirements in more demanding environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 The morphology characteristics and particle size statistics of the aluminum alloy powder material prepared in Example 1.

[0026] Figure 2 This is the metallographic microstructure of the deposited aluminum alloy workpiece prepared in Example 1.

[0027] Figure 3 This is the XRD of the aluminum alloy workpiece prepared in Example 2.

[0028] Figure 4 This is the scanning electron microscope microstructure of the aluminum alloy workpiece prepared in Example 2.

[0029] Figure 5 Transmission electron microscope microstructure and phase size statistics of the aluminum alloy workpiece prepared in Example 2.

[0030] Among them, (a) and (b) are the morphologies under HAADF images; (c) is the morphology under HRTEM mode; and (d) is the secondary Al 3 Size statistics of (Sc,Zr) particles.

[0031] Figure 6 The mechanical properties of the deposited aluminum alloy workpiece prepared in Example 1 and the aluminum alloy workpiece prepared in Example 2. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0034] Combine the following Figure 1-Figure 6 The invention describes the ultra-high strength aluminum alloy powder material and its preparation method and application.

[0035] The embodiment of the present invention first provides an aluminum alloy powder material, wherein the alloy elements thereof include, by mass fraction, Mg 6.5%-10.0%, Sc 0.7%-1.0%, Zr 0.4%-0.7%, Mn 0.40%-1.0%, Si 0.3%-0.7%, trace elements less than or equal to 0.2%, and Al balance.

[0036] The trace elements are selected from one or a combination of two or more of Ti, Fe, Ni, Cu, Cr, Zn and V.

[0037] In a specific embodiment of the present invention, the content of each trace element is less than or equal to 0.03%.

[0038] In a specific embodiment of the present invention, the alloy elements include, by mass fraction, Mg 6.5%-10%, Sc 0.8%-1%, Zr 0.4%-0.5%, Mn 0.45%-1%, Si 0.3%-0.6%, trace elements less than or equal to 0.2% and Al balance.

[0039] In a specific embodiment of the present invention, the Mg content is 6.5% to 10.0%, for example, it can be 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7.0%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8.0%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9.0%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9% and 10.0%, or any value in the range of any value, preferably 6.5% to 10%, and more preferably 8.0% to 10.0%.

[0040] In a specific embodiment of the present invention, the content of Sc is 0.7% to 1.0%, for example, it can be any value of 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95% and 1.00% or a range of any values, preferably 0.7% to 1.0%, and more preferably 0.9% to 1.0%.

[0041] In a specific embodiment of the present invention, the Zr content is 0.4% to 0.7%, for example, it can be any value of 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65% and 0.70%, or a range of any values.

[0042] In a specific embodiment of the present invention, the Mn content is 0.40% to 1.0%, for example, it can be any value of 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95% and 1.00%, or a range of any value, preferably 0.4% to 1.0%, and more preferably 0.8% to 1.0%.

[0043] In a specific embodiment of the present invention, the Si content is 0.3%~0.7%, for example, it can be any value of 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65% and 0.70% or a range of any values, preferably 0.3%~0.4%.

[0044] In a specific embodiment of the present invention, the particle size of the aluminum alloy powder material ranges from 15 μm to 60 μm.

[0045] In a specific embodiment of the present invention, the average sphericity of the aluminum alloy powder material is greater than 0.85.

[0046] In a specific embodiment of the present invention, the hollow powder rate of the aluminum alloy powder material is no more than 5%.

[0047] In a specific embodiment of the present invention, the particle size range of the aluminum alloy powder material is 15μm~60μm, for example, it can be a range consisting of any value of 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm and 60μm.

[0048] In a specific embodiment of the present invention, the average sphericity of the aluminum alloy powder material is greater than 0.85, for example, it can be any value among 0.86, 0.88, 0.90, 0.92, 0.94, 0.96 and 0.98 or a range of any values.

[0049] In a specific embodiment of the present invention, the hollow powder rate of the aluminum alloy powder material is not greater than 5%, for example, it can be any value of 1%, 2%, 3%, 4% and 5%, or a range consisting of any value.

[0050] In a specific embodiment of the present invention, the aluminum alloy powder material has an oxygen content of less than 0.1%, a hydrogen content of less than 0.003%, a carbon content of less than 0.009%, and a nitrogen content of less than 0.03%.

[0051] An embodiment of the present invention also provides a method for preparing the aluminum alloy powder material as described above, comprising: melting and atomizing aluminum raw materials, magnesium raw materials, Al-Si master alloys, Al-Sc master alloys, Al-Zr master alloys and Al-Mn master alloys according to the alloy element quality design of the aluminum alloy powder material.

[0052] In a specific embodiment of the present invention, the aluminum raw material includes pure aluminum with a purity of 99.996%.

[0053] In a specific embodiment of the present invention, the magnesium raw material includes pure magnesium with a purity of 99.96%.

[0054] In a specific embodiment of the present invention, the Al-Si master alloy includes Al-20%Si master alloy.

[0055] In a specific embodiment of the present invention, the Al-Sc master alloy includes Al-2%Sc master alloy.

[0056] In a specific embodiment of the present invention, the Al-Zr master alloy includes Al-5%Zr master alloy.

[0057] In a specific embodiment of the present invention, the Al-Mn master alloy includes Al-10%Mn master alloy.

[0058] In a specific embodiment of the present invention, according to the quality design of the alloying elements of the aluminum alloy powder material, aluminum raw material, magnesium raw material, Al-Si master alloy, Al-Sc master alloy, Al-Zr master alloy and Al-Mn master alloy are sequentially placed in a vacuum induction melting crucible for melting and high-fluidity atomization, and then the initially obtained ultra-high-strength aluminum alloy powder is dried, sieved or airflow graded, and packaged and sealed for storage to obtain the aluminum alloy powder material.

[0059] In a specific embodiment of the present invention, the smelting includes: vacuum induction melting.

[0060] In a specific embodiment of the present invention, the vacuum degree of the vacuum induction melting is ≤0.5×10 -2 Pa.

[0061] In a specific embodiment of the present invention, the melting temperature of the vacuum induction melting is 850°C-950°C.

[0062] In a specific embodiment of the present invention, the heating rate of the vacuum induction melting is 8°C / min~20°C / min.

[0063] In the present invention, in order to achieve a better smelting effect, generally, during the heating process, the temperature can be preset at a value about 50°C lower than the smelting temperature, and the temperature can be kept uniform for a certain period of time, and then the temperature is continued to be raised to the smelting temperature for smelting. The smelting time is generally 10 to 20 minutes, preferably 16 minutes.

[0064] In a specific embodiment of the present invention, the atomization includes: high-flowability atomization.

[0065] In a specific embodiment of the present invention, the oxygen content of the atomization is controlled below 200 ppm.

[0066] In a specific embodiment of the present invention, the inert gas introduced by atomization is 99.9999% high-purity Ar gas.

[0067] In a specific embodiment of the present invention, the atomization pressure of the atomization is 6MPa~15MPa.

[0068] In a specific embodiment of the present invention, the drying temperature of the powder is 80°C to 180°C, preferably 120°C.

[0069] In a specific embodiment of the present invention, the drying includes: vacuum drying.

[0070] In a specific embodiment of the present invention, the vacuum degree of the vacuum drying is ≤500Pa, preferably 300Pa.

[0071] In a specific embodiment of the present invention, the drying time is 3h~7h, preferably 5h.

[0072] In a specific embodiment of the present invention, the screening includes vibration screening.

[0073] In a specific embodiment of the present invention, the screen of the screening device includes screens for separating powder particles with a particle size of ≤15 μm and powder particles with a particle size of ≥60 μm.

[0074] In a specific embodiment of the present invention, the sieve for separating powder particles with a particle size of ≤15 μm is 500-1000 mesh, preferably 1000 mesh.

[0075] In a specific embodiment of the present invention, the sieve used for separating powder particles with a particle size of ≥60 μm is 250 mesh to 300 mesh, preferably 250 mesh.

[0076] This embodiment also provides a deposited aluminum alloy workpiece, which is prepared by an additive manufacturing method, and its raw materials include: the aluminum alloy powder material as described above; the additive manufacturing method includes a laser powder bed melting method.

[0077] In a specific embodiment of the present invention, the tensile strength of the deposited aluminum alloy workpiece is 475MPa~515MPa, the yield strength is 440MPa~490MPa, and the elongation is 14%~30%.

[0078] The present invention also provides a method for preparing a deposited aluminum alloy workpiece, comprising: its raw materials include: the aluminum alloy powder material as described above, or the aluminum alloy powder material prepared by the preparation method as described above.

[0079] The raw material is deposited on an aluminum alloy substrate by using a laser powder bed melting method to obtain the deposited aluminum alloy workpiece.

[0080] In a specific embodiment of the present invention, in the laser powder bed melting method, the laser spot diameter is 100 μm, the laser power is 180W~380W, the laser beam scanning speed is 800mm / s~1400mm / s, the scanning interval is 0.10mm~0.15mm, and the layer thickness is 25~40 μm.

[0081] In a specific embodiment of the present invention, the preheating temperature of the aluminum alloy substrate is 80°C-160°C.

[0082] In a specific embodiment of the present invention, the laser power is 180W~380W, for example, it can be any value of 180W, 190W, 200W, 210W, 220W, 230W, 240W, 250W, 260W, 270W, 280W, 290W, 300W, 310W, 320W, 330W, 340W, 350W, 360W, 370W and 380W, or a range of any values.

[0083] In a specific embodiment of the present invention, the laser beam scanning speed is 800mm / s~1400mm / s, for example, it can be any value of 800mm / s, 900mm / s, 1000mm / s, 1100mm / s, 1200mm / s, 1300mm / s, 1400mm / s or a range of any values.

[0084] In a specific embodiment of the present invention, the scanning interval is 0.10 mm to 0.15 mm, for example, it can be any value among 0.10 mm, 0.11 mm, 0.12 mm, 0.13 mm, 0.14 mm and 0.15 mm, or a range consisting of any values.

[0085] In a specific embodiment of the present invention, the layer thickness is 25-40 μm, for example, it can be any value among 25 μm, 30 μm, 35 μm and 40 μm, or a range consisting of any values.

[0086] In a specific embodiment of the present invention, the preheating temperature of the aluminum alloy substrate is 80°C~160°C, for example, it can be any value of 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C and 160°C or a range of any values.

[0087] In a specific embodiment of the present invention, the laser powder bed melting method is used to deposit the raw material on the aluminum alloy substrate to obtain the deposited aluminum alloy workpiece, and then an aging treatment is performed. The process can be: the ultra-high strength aluminum alloy powder finally obtained is subjected to laser powder bed melting to form a product. 5052 castings or aluminum forgings are used as substrate materials, which are installed in the forming chamber after polishing and cleaning for use, and the substrate is preheated. The forming chamber of the powder bed melting equipment is purged with inert gas to the required vacuum degree, and the purging is continued until the oxygen content in the forming chamber is controlled below 100ppm during the entire powder bed melting deposition process, and printing is started under the printing parameters. After the deposition is completed, the protective atmosphere is continued to be introduced until it is cooled to room temperature and then the chamber is opened and taken out.

[0088] The furnace samples and workpieces are cut off with a wire cutting machine and then subjected to aging treatment in a heat treatment furnace.

[0089] The present invention also provides an aluminum alloy workpiece, which is obtained by using a laser powder bed melting method to prepare a deposited aluminum alloy workpiece, and then performing an aging treatment, including: its raw materials include: the aluminum alloy powder material as described above, or the aluminum alloy powder material prepared by the preparation method as described above.

[0090] In a specific embodiment of the present invention, the microstructure of the aluminum alloy workpiece includes a bimodal grain structure of equiaxed crystals and columnar crystals, and discontinuous micron-sized Mg 2 Si、Al 6 Mn particles and nano-scale Al 3 (Sc, Zr) particles.

[0091] In a specific embodiment of the present invention, the average width of the nano-scale Al3 (Sc, Zr) particles is 1.1 nm to 1.3 nm.

[0092] In a specific embodiment of the present invention, the aluminum alloy workpiece has a tensile strength of 600 MPa or more, a yield strength of 560 MPa or more, and an elongation of 8% or more.

[0093] In a specific embodiment of the present invention, the tensile strength is 600MPa~650MPa, the yield strength is 560MPa~630MPa, and the elongation is 8%~13%.

[0094] This embodiment also provides a method for preparing an aluminum alloy workpiece, which adopts a laser powder bed melting method to prepare a deposited aluminum alloy workpiece, and then performs an aging treatment. The raw materials include: the aluminum alloy powder material as described above, or the aluminum alloy powder material prepared by the preparation method as described above.

[0095] In a specific embodiment of the present invention, the deposited aluminum alloy workpiece is the deposited aluminum alloy workpiece as described above or a deposited aluminum alloy workpiece prepared by the preparation method as described above.

[0096] In a specific embodiment of the present invention, the aging treatment includes: an aging temperature of 275°C to 375°C, a holding time of 1h to 8h, and air cooling; more preferably, an aging temperature of 275°C to 325°C, a holding time of 2h to 8h, and air cooling.

[0097] In a specific embodiment of the present invention, the aging temperature is 275°C to 375°C, for example, it can be any value of 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C, 320°C, 325°C, 330°C, 335°C, 340°C, 345°C, 350°C, 355°C, 360°C, 365°C, 370°C and 375°C, or a range of any values.

[0098] In a specific embodiment of the present invention, the insulation time is 1h~8h, for example, it can be any value of 1h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h and 8h, or a range of any values.

[0099] In a specific embodiment of the present invention, the aging treatment includes: an aging temperature of 300° C., a heat preservation time of 4 hours, and air cooling.

[0100] The ultra-high-strength aluminum alloy powder material of the present invention, its preparation method and application are described in detail below with reference to specific cases.

[0101] Example 1 The present embodiment provides an aluminum alloy powder material. The elements of the aluminum alloy powder material are designed to be, by mass fraction, Mg: 6.5%, Sc: 1.0%, Zr: 0.4%, Mn: 1.0%, Si: 0.3%, and the remainder is Al.

[0102] This embodiment provides a method for preparing the above aluminum alloy powder material, which is specifically as follows: According to the above composition formula, based on mass fraction, 99.996% pure aluminum, 99.96% pure magnesium, Al-20% Si master alloy, Al-2% Sc master alloy, Al-5% Zr master alloy, and Al-10% Mn master alloy with set mass proportions are selected.

[0103] The above raw materials are placed in a vacuum chamber with a degree of vacuum of 0.2×10 -2 In a Pa induction melting crucible, the oxygen content was set to 150 ppm, the heating rate was 10°C / min, the melting temperature was 900°C, the holding temperature was 950°C and the holding time was 20 min, and melting and high-fluidity atomization were performed to obtain the initial ultra-high strength aluminum alloy powder.

[0104] Secondly, the initially obtained ultra-high strength aluminum alloy powder was dried in a drying device at a temperature of 120° C. and a vacuum degree of 500 Pa for 4 hours.

[0105] Then, the dried initial ultra-high strength aluminum alloy powder is vibrated and sieved; specifically: large particles of powder larger than 60 μm are sieved out through a 250-mesh sieve; small particles of powder less than 15 μm are sieved out through a 1000-mesh sieve, and the powder is packaged, sealed and stored to obtain aluminum alloy powder with high sphericity (average sphericity > 0.85) and low hollow powder rate (not more than 5%) that meets the requirements of laser powder bed melting.

[0106] The chemical composition of the aluminum alloy powder obtained by testing is shown in Table 1 below.

[0107] Table 1

[0108] Furthermore, the morphology of the obtained aluminum alloy powder was characterized. Figure 1 Its particle size distribution is shown in Figure 1 As shown in (b), it can be seen that the particle size distributions of D10, D50 and D90 of the aluminum alloy powder are 19.16 μm, 33.46 μm and 55.28 μm, respectively.

[0109] The present embodiment also provides an application of the above-mentioned aluminum alloy powder material, including: using a laser powder bed melting method to deposit the above-mentioned aluminum alloy powder material on an aluminum alloy substrate to obtain a deposited aluminum alloy workpiece, the specific process is: the surface of the 5052 forging substrate is polished with 120-mesh sandpaper until it is non-reflective, and then the surface of the substrate is cleaned with acetone, the laser is a fiber laser with a maximum power of 500W, a spot diameter of 100μm, a laser power of 330W, a scanning speed of 1200mm / s, a scanning spacing of 0.11mm, a layer thickness of 30μm, and a substrate preheating temperature of 100°C.

[0110] The alloy composition of the deposited aluminum alloy workpiece obtained by electron probe technology is Al-6.5Mg-1Sc-0.4Zr-1Mn-0.3Si, wt.%, and its metallographic microstructure is as follows: Figure 2 shown.

[0111] The mechanical properties of the deposited aluminum alloy workpiece were tested in accordance with the national standard GB / T 228.1-2010 "Metallic materials tensile test part 1 room temperature test method" and the results are shown in Table 2.

[0112] Table 2

[0113] The room temperature tensile mechanical properties test results of the deposited aluminum alloy workpiece obtained in Example 1 are shown in FIG. Figure 6 shown.

[0114] Example 2 This embodiment provides a method for preparing an aluminum alloy workpiece. Based on Example 1, the obtained deposited aluminum alloy workpiece is subjected to heat treatment, i.e., aging treatment, with the following parameters: aging temperature of 300°C, holding time of 4h, and air cooling to obtain the aluminum alloy workpiece.

[0115] The aluminum alloy workpiece obtained by testing has the following results: Figure 3 The XRD results of the aluminum alloy workpiece prepared in Example 2 show that after heat treatment, the aluminum alloy workpiece has α-Al and Al 3 (Sc, Zr), Mg 2 Si and Al 6 Mn phase.

[0116] Figure 4 The scanning electron microscope microstructure characteristics of the aluminum alloy workpiece prepared in Example 2.

[0117] Figure 5 Figures (a) and (b) are the morphologies of the microstructure of the aluminum alloy workpiece prepared in Example 2 under TEM imaging mode, showing the bimodal grain structure morphology and the discontinuous Mg at the grain boundary.2 Si and Al 6 Mn particles. Figure 5 Figure (c) shows the morphology under HRTEM mode, where secondary Al 3 (Sc, Zr) particles. (d) The secondary Al 3 (Sc, Zr) particle size statistics. Among them, Al 3 The average width of the (Sc,Zr) nanoparticles is about 1.21 nm.

[0118] According to GB / T 228.1-2010 "Metallic Materials Tensile Test Part 1 Room Temperature Test Method", the aluminum alloy workpiece prepared in Example 2 was tested for mechanical properties. The results are shown in Table 3 and the room temperature tensile mechanical properties test results are shown in the figure. Figure 6 shown.

[0119] Table 3

[0120] Example 3 This embodiment optimizes some data of printing process parameters without changing the composition formula of embodiment 1, and other conditions are the same as those of embodiment 1. The process parameters and performance are specifically shown in Table 4. Each serial number represents a set of process parameters.

[0121] Table 4

[0122] Example 4 This example is based on Example 2, and the partial data of aging for 4 hours at different temperatures of 275°C to 375°C are obtained. Other conditions are the same as those of Example 2. The heat treatment temperature and performance are specifically shown in Table 5. Each serial number represents a set of process parameters.

[0123] Table 5

[0124] Example 5 This embodiment 5 is based on the embodiment 2, and the aging is carried out under the temperature of 300°C for different time conditions. The other conditions are the same as those of the embodiment 2. The heat treatment temperature and performance are shown in Table 6. Each serial number represents a set of process parameters.

[0125] Example 6 This embodiment 6 optimizes the alloy composition on the basis of embodiment 2, and other conditions are the same as those of embodiment 2. The room temperature tensile properties regardless of alloy composition are shown in Table 7. Each serial number represents a group of alloy compositions.

[0126] It can be seen from the data in Table 7 that the alloy composition range in which the microhardness is significantly improved after aging treatment is: Mg 6.5%~10%, Sc 0.8%~1%, Zr 0.4%~0.5%, Mn 0.45%~1%, Si 0.3%~0.6%, trace elements less than or equal to 0.2% and Al balance.

[0127] The present invention comprehensively considers the multi-stage process coordination means such as component design and process preparation based on crack resistance and strength-toughness synergy, printing process and heat treatment, and innovatively proposes an additive manufacturing ultra-high strength aluminum alloy powder and its preparation method and application in additive manufacturing ultra-high strength aluminum alloy workpieces, breaking through the 600MPa ultra-high strength level, while synergizing the excellent balance of strength and ductility, reducing the yield strength ratio, and meeting the needs of engineering components. This invention greatly fills the market gap of 600MPa-level strength additive manufacturing aluminum alloys, which has far-reaching significance for the needs of major equipment such as aerospace.

[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An aluminum alloy powder material, characterized in that: Calculated by mass fraction, the alloying elements include: Mg 6.5%~10.0%, Sc 0.7%~1.0%, Zr 0.4%~0.7%, Mn 0.40%~1.0%, Si 0.3%~0.7%, trace elements less than or equal to 0.2% and Al balance.

2. The aluminum alloy powder material according to claim 1, characterized in that: The particle size of the aluminum alloy powder material ranges from 15 μm to 60 μm; And / or, the average sphericity of the aluminum alloy powder material is greater than 0.85; And / or, the hollow powder rate of the aluminum alloy powder material is not more than 5%.

3. The method for preparing the aluminum alloy powder material according to claim 1 or 2, characterized in that: include: Aluminum raw materials, magnesium raw materials, Al-Si master alloy, Al-Sc master alloy, Al-Zr master alloy and Al-Mn master alloy are melted and atomized according to the alloy element quality design of the aluminum alloy powder material.

4. The method for preparing aluminum alloy powder material according to claim 3, characterized in that: The smelting includes: vacuum induction melting; Preferably, the vacuum degree of the vacuum induction melting is ≤0.5×10 -2 Pa; Preferably, the melting temperature of the vacuum induction melting is 850°C to 950°C; Preferably, the heating rate of the vacuum induction melting is 8°C / min to 20°C / min.

5. A deposited aluminum alloy workpiece, prepared by an additive manufacturing method, characterized in that: The raw materials include: the aluminum alloy powder material according to claim 1 or 2, or the aluminum alloy powder material prepared by the preparation method according to claim 3 or 4; the additive manufacturing method includes a laser powder bed melting method; Preferably, the deposited aluminum alloy workpiece has a tensile strength of 475 MPa to 515 MPa, a yield strength of 440 MPa to 490 MPa, and an elongation of 14% to 30%.

6. A method for preparing a deposited aluminum alloy workpiece, characterized in that: include: The raw materials include: the aluminum alloy powder material according to claim 1 or 2, or the aluminum alloy powder material prepared by the preparation method according to claim 3 or 4; The raw material is deposited on an aluminum alloy substrate by a laser powder bed melting method to obtain the deposited aluminum alloy workpiece; Preferably, in the laser powder bed fusion method, the laser spot diameter is 100 μm, the laser power is 180 W to 380 W, the laser beam scanning speed is 800 mm / s to 1400 mm / s, the scanning interval is 0.10 mm to 0.15 mm, and the layer thickness is 25 to 40 μm; Preferably, the preheating temperature of the aluminum alloy substrate is 80°C to 160°C.

7. An aluminum alloy workpiece, obtained by laser powder bed fusion to obtain a deposited aluminum alloy workpiece, followed by aging treatment, characterized in that: include: The raw materials include: the aluminum alloy powder material described in claim 1 or 2, or the aluminum alloy powder material prepared by the preparation method described in claim 3 or 4.

8. The aluminum alloy workpiece according to claim 7, characterized in that: The microstructure of the aluminum alloy workpiece includes a bimodal grain structure of equiaxed crystals and columnar crystals, discontinuous micron-sized Mg2Si and Al6Mn particles at the grain boundaries, and nanometer-sized Al3 (Sc, Zr) particles within the crystals; Preferably, the average width of the nano-sized Al3(Sc,Zr) particles is 1.1 nm to 1.3 nm.

9. The aluminum alloy workpiece according to claim 7 or 8, characterized in that: The aluminum alloy workpiece has a tensile strength of 600 MPa or more, a yield strength of 560 MPa or more, and an elongation of 8% or more; Preferably, the tensile strength is 600MPa~650MPa, the yield strength is 560MPa~630MPa, and the elongation is 8%~13%.

10. A method for preparing an aluminum alloy workpiece, comprising: preparing a deposited aluminum alloy workpiece by laser powder bed fusion method, and then performing aging treatment, wherein: The raw materials include: the aluminum alloy powder material according to claim 1 or 2, or the aluminum alloy powder material prepared by the preparation method according to claim 3 or 4; Preferably, the deposited aluminum alloy workpiece is the deposited aluminum alloy workpiece according to claim 5 or a deposited aluminum alloy workpiece prepared by the preparation method according to claim 6; Further preferably, the aging treatment includes: an aging temperature of 275°C to 375°C, a holding time of 1h to 8h, and air cooling; more preferably, the aging temperature is 275°C to 325°C, a holding time of 2h to 8h, and air cooling.

Citation Information

Cited By

  • Laser powder bed molten nano amorphous particle reinforced aluminum matrix composite and method and application thereof

    CN120776169A

  • Laser powder bed fusion of nanocrystalline amorphous particle reinforced aluminum matrix composites, methods, and applications

    CN120776169B